Hubungan Self Control dengan Toxic Online Disinhibition pada Remaja Pengguna Instagram di Sumatera Barat - Muhammad Iqbal Firmansyah; Yuninda Tria Ningsih (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2026)
The widespread use of social media has created new dynamics in adolescent social interactions, one of which is the emergence of the phenomenon of toxic online disinhibition, a psychological dynamic that causes differences in destructive behavior in the digital space. This phenomenon is found to be widespread among adolescent Instagram users in West Sumatra, most of whom are still in an unstable phase of self-control development. This study is important to examine the extent of the relationship between self-control and toxic online disinhibition in adolescent Instagram users. The research method used is a quantitative correlational approach with a sample of 400 adolescents aged 13–18 years selected using a cluster sampling technique. Data were collected using two scales: the self-control scale (Tangney et al., 2004) and the toxic online disinhibition scale (Udris, 2014 adapted by Mantara et al., 2023), and analyzed using the Pearson Product Moment correlation technique. The results show a negative relationship between self-control and toxic online disinhibition, meaning that the lower the adolescent's self-control ability, the lower their tendency to display negative behavior on Instagram.